INTERACTOMICS IN TRANSLATIONAL MEDICINE - A. I. Glukhov; Z. A. Khuchua; G. K. Grizunova; D. V. Astakhov; M. I. Danilevskiy (Сеченовский вестник, 2018)
The article describes the place of interactomics in translational medicine. The approaches and methods used for the detection of protein-protein interactions and the construction of interactomes are described. Examples of electronic databases that work with interactomes are given, as well as examples of consortia of such databases. Examples of the use of interactomes for developing new approaches and methods of treatment of such diseases as cancer, diabetes, schizophrenia are considered. The main difficulties encountered in the construction of interactomes, and the prospects for the development of interactomics are outlined.